Evaluation of efficiency of correction climacteric syndrome in women of perimenopausal period with reproductive disturbances in anamnesis - С. О. Шурпяк; В. І. Пирогова; М. Й. Малачинська (Publishing House TRILIST, 2017)
The article deals with the issues of application of menopausal hormone therapy (MHT) in women of perimenopausal age with menopausal syndrome and reproductive disorders in the anamnesis. 46 women with moderate or severe degree of climacteric syndrome and reproductive disorders in the anamnesis (the main group) who received the drug Climonorm on a three-week schedule with a seven-day break were examined. The comparison group consisted of 19 patients of the same age who had contraindications to the use of MHT. In a reproductive history in patients marked loss of pregnancy at different gestational age; PID; operative interventions for benign ovarian tumors, ectopic pregnancy, genital endometriosis, infertility; abnormal uterine bleeding, not associated with pregnancy or the presence of uterine fibroids. During the period of inclusion in the study, 38.5% of women were regular menstrual circle (MC), 15.4% reported intermenstrual bleeding, 18.5% had hyperpolymenorrhea, and 27.6% had acyclical uterine bleeding of varying intensity. Patients showed complaints of hot flashes, night sweats, sleep disturbances, headache, dizziness, emotional lability, depression, fatigue, muscle and joint pain. Before the beginning of therapy, the severity of menopausal syndrome according to MMI was 47.0 ± 6.1 in the main group, in the comparison group - 45.3 ± 6.9. In the case of MC disorders, a pendulum biopsy of the endometrium or hysteroscopy with separate diagnostic scraping of the walls of the cavity and cervix of the uterus was performed. Morphological examination in 67.9% of cases verified endometrium in the stage of proliferation, in 32.1% - simple non-atypical endometrial hyperplasia. After 6 months of treatment, the patients of the main group had a pronounced positive dynamics of climacteric complaints, the average value of MMI after treatment decreased from 47.0 ± 6.1 to 10.2 ± 1.4 points (p <0.001). In a dynamic US examination, the negative dynamics of M-echo indices was not recorded, 86.3% of women with MC disorders before the start of treatment noted regular menstrual bleeding in the interval between the Climonorm doses. MHT with the use of the Climonorm allows to effectively reduce the severity of manifestations of the climacteric syndrome by 80-60%, ensures the regularity and stability of the MC. The appointment of a cyclic combination of MHT with a strong progestogen component (levonorgestrel) has advantages in women with non-atypical hyperplastic processes in the perimenopause, since it prevents recurrence of uterine bleeding with a reduction or complete reduction of menopausal symptoms and no adverse effect on the endometrium.